Trauma Psikososial Tokoh Utama Dalam Memoar Broken Strings Karya Aurelie Moeremans: Kajian Psikologi Trauma - Dafin Firly Althaf; Anas Ahmadi (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2026)
This study aims to describe the forms of psychosocial trauma experienced by the main character in the memoir Broken Strings by Aurelie Moeremans and to analyze their impact on the character's psychological condition and social life based on Judith Lewis Herman's trauma theory. This research employed a descriptive qualitative approach using the content analysis method. The data consisted of narratives, dialogues, and monologues representing the main character's traumatic experiences. Data were collected through reading and note-taking techniques and analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the main character experiences five forms of psychosocial trauma: intrusion, constriction, hyperarousal, interpersonal disturbance, and self-blame. These traumatic experiences lead to impaired concentration, decreased self-confidence, negative self-image, difficulties in establishing social relationships, and prolonged fear. Nevertheless, the main character gradually undergoes a recovery process by realizing that the violence experienced was not her fault, enabling her to reconstruct a more positive self-identity. This study confirms that Judith Lewis Herman's trauma theory is highly relevant for examining the representation of psychosocial trauma in contemporary literary works, particularly those depicting manipulative and abusive interpersonal relationships.